PERTUMBUHAN DAN KELANGSUNGAN HIDUP BENIH IKAN GABUS (Channa striata) YANG DIBERI BERBAGAI JENIS ATRAKTAN - Muhamad Zainuri; Mirna Fitrani; Yulisman . (Universitas Sriwijaya, 2017)
ABSTRACT The addition of atractant in feed is expected could improve snakehead respond,andincreasing its growth. The Aims of this study are to knowfeed respond, the feed intake, growth, feed efficiency, and survival rate of snakehead fry given by feed with different various of atractant.This research was conducted on Jun-July 2016 at Laboratorium Dasar Perikanan Program Study Budidaya Perairan, Agriculture Faculty, Sriwijaya University. This research was using completely randomized designed with four treatments and three replications, consist offeed without attractants (P0), feed with 2% fish meal addition (P1), feed with 2% squid meal addition (P2), and feed with 2% shrimp meal addition (P3). Fish maintained for 30 days and fed four times a day (at 07.00, 11.00, 14.00 and 17.00) are at satiation. Parameters of this research are feed respond, the feed intake, growth, feed efficiency and survival rate of snakehead fry. The result showed that given of atractant effect to feed intake and absolute growth of weight (Channa striata) fry, yet did not give effect to snakehead respond significantly, for absolute growth of length, feed efficency and survival rate. The best treatment was P3 (feed with 2% shrimp meal addition) with feed intake was 17.19 g, absolute growth of weight was 0.52 g, absolute growth of length was 1.33 centimetre, survival rate was 73.33% and feed efficiency was 48.97%. Physical and chemical of media maintanace, temperature 25-28oC, pH was 6.35-6.96, DO was 5.05-5.96 mg.L-1 and ammonia 0.02-0.17 mg.L-1. Keywords : Atractant, Channa striata, Growth and feed respond